PERAN GURU PPKn DALAM PEMBENTUKAN KARAKTER SISWA DI SMP TEUKU UMAR - wahyuni, sri; Marif, Abdul; Siregar, Disna Anum; Fatahillah, Raja F. (Universitas Muhammadiyah Bengkulu, 2025)
Teachers have a central role in shaping students' character, not only as a transmitter of material, but also as a role model. Pancasila and Citizenship Education (PPKn) functions to instill moral, aesthetic, and character values ​​based on Pancasila, especially the second principle, namely just and civilized humanity. This study aims to determine the role of PPKn teachers in shaping the character of grade VIII students at SMP Teuku Umar, with a focus on religious values, nationalism, independence, mutual cooperation, and integrity. The method used is quantitative descriptive through observation, interviews, and questionnaires. The results of the study indicate that PPKn teachers play an important role in shaping students' character through learning, habituation, and role models. The obstacles faced include low student motivation and limited facilities. Effective strategies applied include a persuasive approach and consistent reinforcement of values. These findings emphasize the importance of the role of PPKn teachers in shaping a generation with character according to Pancasila values.